Laura Wingate: capstone - Wingate, Laura, artist (Colorado State University. Libraries, 2014)
The artist's statement: My art is a collection of stories stemming from my own personal narrative. Told through an ink world of animal hybrids, my hope is for the work to transport the viewer into nostalgic and strange folklore. These fables speak of distant sounds somewhere in the deep, dark forest, the rustling of moonlit leaves, and the howl which echoes from somewhere in the back of our minds. From the frightened doe that startles at the very hint of danger and the humble and lamb hearted, to the wise yet mischievous sage, the animals in this torn paper world are depictions of the people and themes present within my own story. The creatures I scrawl upon the page tell tales of vulnerability, fragility, and yearning. Their ink faces are something more than scribbled and something less than written. They are pure, they are primal, they are immediate, they are drawn. However cryptic these tales may be, however wild the lines become, it is clear these heartfelt creatures are in search of something more, just like the rest of us.
Strange but familiar: the art work of Laura Wingate
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.